Determination of insecticide resistance in cotton whitefly in north India - S, RAJNA; MAHAPATRO, G K; SUBRAMANIAN, S; CHANDER, SUBASH (The Indian Journal of Agricultural Sciences, 2024)
The whitefly, Bemisia tabaci (Gennadius) considered as most destructive pest, poses a significant threat to various crop species globally has developed resistance due to the indiscriminate use of synthetic chemicals. A study was carried out in 2018 at ICAR-Indian Agricultural Research Institute, New Delhi to determine insecticide resistance, in five Asia II 1 populations of B. tabaci from different cotton (Gossypium hirsutum L.) growing regions of north India. The susceptibility of the populations to different insecticide classes, viz. synthetic pyrethroid (cypermethrin); neonicotinoids (imidacloprid and thiamethoxam); thiourea (diafenthiuron) and diamide (cyantraniliprole) were assessed. Results revealed substantial heterogeneity in the responses of these populations to the insecticides. Sriganganagar and Bathinda populations exhibited moderate resistance to cypermethrin, imidacloprid, and thiamethoxam. Low level of resistance was observed in Bathinda and Sriganganagar populations against diafenthiuron. All populations were highly susceptible to cyantraniliprole. No cross-resistance was observed between cyantraniliprole and other insecticides, suggesting its potential as an alternative for managing insecticide resistance. High levels of detoxification enzymes (esterase, cytochrome P450 monooxygenase, and glutathione-S-transferase) in Sriganganagar and Bathinda populations indicated a positive correlation between insecticide resistance and detoxifying enzymes. These findings offer valuable insight for implementing insecticide rotation strategies to combat B. tabaci resistance in India.